Efektifitas Limbah Kulit Nangka Dan Kotoran Sapi Pada Pupuk Organik Padat Dengan Fermentasi Menggunakan Bioaktivator Effective Mikroorganisme 4 (EM4) - Ali Fathu Rohman; Fitri Kamila; Firda Febriani (Politeknik Negeri Cilacap, 2023)
The jackfruit chip industry in Cilacap produces one ton of processed per week. This production, besides producing processed jackfruit chips, it also produces waste in the form of jackfruit skin and jackfruit. If it is not processed and if it is disposed of into the environment, it will take a long time to decompose and cause a bad smell to humans. To overcome this waste, it is made into organic fertilizer. Organic fertilizers are fertilizers derived from various natural ingredients such as animal manure, animal body parts, plants, which are rich in organic compounds and are good for the use of soil enrichment. This study aims to determine the effectiveness of cow dung and fruit waste in the manufacture of solid organic fertilizer by fermentation using the EM4 bioactivator, which was tested with chemical parameters such as C-Organic, water content, temperature and pH. The manufacture of solid organic fertilizer can be done by decomposing jackfruit skin waste and cow dung waste by fermentation using EM4 and molesses with ratio 1 :1 then observed for four weeks. Based on the research results, it can be seen that the temperature, pH, water content and C-organic content are in accordance with the quality standards of organic fertilizers. The highest organic C content was found in the second week of 60.87 and then decreased to 37,58.